Investigation of the Compression and Dielectric strength properties for Epoxy/Polyurethane Blends reinforced with glass fibers - Jawad, Mohammed K (Al-Nahrain Journal of Science, 2013)
الخلاصة: Compression and dielectric strength properties of EP/PU blends composites reinforced with two layers of random direction glass fibers have been investigated. Hand lay up method was used to prepare sheets of EP/PU blends composites with different weight percentage of PU(12.5%,25% and37.5%). Results show that the compression value increase with the increasing of the weight percentage of PU in the blended matrix composite and became higher than for epoxy composite, while the results of the dielectric strength show that its values decrease with the increasing of the PU weight percentage in the blended matrix composite .